Three‐Dimensional Surface Displacements During the 2016 MW 7.8 Kaikōura Earthquake (New Zealand) From Photogrammetry‐Derived Point Clouds. Issue 1 (20th January 2020) - Howell, A.; Nissen, E.; Stahl, T.; Clark, K.; Kearse, J.; Van Dissen, R.; Villamor, P.; Langridge, R.; Jones, K.
Abstract: High‐resolution, three‐dimensional (3‐D) measurements of surface displacements during earthquakes can provide constraints on fault geometry and near‐surface slip and also quantify on‐fault and off‐fault deformation. However, measurements of surface displacements are often hampered by a lack of high‐resolution preearthquake elevation data, such as lidar. For example, preearthquake lidar for the 2016 M W 7.8 Kaikōura, New Zealand, earthquake only covers ≲10% of ~180 km of mapped surface ruptures. To overcome a lack of preearthquake lidar, we measure 3‐D coseismic displacements during the Kaikōura earthquake using point clouds generated from aerial photographs. From these point clouds, which cover the whole area of the 2016 surface ruptures, it is possible to measure 3‐D displacements to within ±0.2 m. We measure coseismic slip and estimate the geometries of faults in the steep, inaccessible Seaward Kaikōura mountains, where postearthquake field observations are very sparse. The Jordan Fault (previously the Jordan Thrust) ruptured in 2016 as a moderate‐to‐steeply dipping (~50–80°), predominantly strike‐slip fault. Slip on this fault in 2016—which included a normal‐sense component in some areas—contrasts with field observations that indicate significant longer‐term shortening across the Jordan Fault during the Holocene. It is therefore likely that different earthquakes on the Jordan Fault have very different slip vectors and that the fault does not exhibit "characteristic" slip behavior. For faults like the Jordan Fault, long‐term time‐averaged estimates of slip rate may not be reliable indicators of the sense and magnitude of slip in individual earthquakes. Key Points: High‐resolution, three‐dimensional surface displacements during earthquakes can be measured from aerial photographs The Jordan Fault did not accommodate significant shortening in an earthquake in 2016 but probably does in the long term